If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1n + -13 = -23 Reorder the terms: -13 + -1n = -23 Solving -13 + -1n = -23 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1n = -23 + 13 Combine like terms: -13 + 13 = 0 0 + -1n = -23 + 13 -1n = -23 + 13 Combine like terms: -23 + 13 = -10 -1n = -10 Divide each side by '-1'. n = 10 Simplifying n = 10
| x(5+8)=39 | | 3n+3.1=8.8 | | 0=ln(x+2) | | 2(n-3)=-26 | | 36x+6y=450 | | a+4b-2a-b= | | 18x-6y=90 | | -3n+1=31 | | 3n+2p=6 | | -34=-2x+4(3x+4) | | 9(y-3)=8y | | 5(1+.2y)-y=5 | | 4y+3y=6y-8 | | 9-5=-3 | | v^2-30=-v | | 10=-4x-4 | | 9(e-8)=9 | | (6-3i)+(2+7i)=0 | | 3(x-8)=2(x-3) | | 7(q-7)=7 | | 5n+2p=9 | | 5c+27=87 | | 3x+3=124 | | 6x^2-18-108=0 | | .75w=.7 | | 2(2x-2)=-12 | | 10t+8=-12 | | 8(x-6)=7x-9 | | 24-10x=2x | | w(2w-15)-225=0 | | 6-4y=50 | | 6f-9=-57 |